An Advanced Appliance Interaction Architecture - O'Sullivan, Darragh (Trinity College Dublin. Department of Computer Science, 2005)
In the future, the ability to monitor and control home appliances over the Internet could become one of the conveniences that we wonder how we ever managed without. Also, the ability to interact with networked appliances within the home, using different user devices and modalities, could prove to be hugely beneficial to certain users, especially the disabled and elderly. Using a single device to discover and communicate multi-modally with many appliances based on different technologies could bring untold advantages to such people. There are a number of issues however, preventing these scenarios from being realised. The dissertation firstly presents these challenges along with the requirements that need to be met. There are three main challenges that need to be addressed. The first challenge is communication in a heterogeneous environment where there are a variety of communication protocols being used by the networked appliances (Jini, HAVi, UPnP and many more). Secondly, it is also expected that there will be a broad range of user devices in operation in future home and vehicle networks. Users will come to expect visual, speech and possibly even gesture interaction all at once. Thus, multi-modal and multi-device interaction is required. This leads to research in generic user interface languages. Lastly, for the true value of networked appliances to be realised, wide-area access to appliances over the Internet should be provided and currently there is very poor support for this. This dissertation reviews the state-of-the-art in multi-modal interaction, heterogeneous communication and wide-area access to networked appliances. Based on an analysis of the requirements and state-of-the-art, an appliance interaction architecture is pro- posed. The service-oriented OSGi (Open Services Gateway Initiative) framework is proposed as the basis of the architecture. OSGi is a standardised, protocol agnostic, lightweight services gateway. It has widespread industry support, and it provides a dynamic services platform allowing components such as appliance drivers and user interface transcoders to be deployed at run-time. As an evaluation of the feasibility of the proposed architecture, a proof-of-concept implementation is deployed and evaluated on the Oscar OSGi framework. It is established that an appliance interaction architecture implemented on the OSGi framework is a flexible environment for deploying services in a home or vehicle network.
Keywords: Computer Science